دراسة أسباب أوامر التغيير وكيفية تلافي تأثيرها السلبي في مشاريع التشييد - مصطفى, ماهر; الحريري, محمود (Latakia University Journal -Engineering Sciences Series, 2016)
Changes in construction projects are considered as prevalent phenomenon. Where, most of projects face changes in drawings, specifications, work scope, or contractual conditions. The traditional construction followed in Syrian projects has a long time span between planning, design, and construction. As result the possibility of changes occurrence in any project becomes considerable. There are many causes of change orders in construction industry. These changes, mostly causes time and cost overrun and managerial complications.The objective of this study is determining the main causes of change orders; arranging them according to their significance; and studying their effects on project’s cost and time. The owner or the engineer supervising the project is the party who is responsible for change orders in the projectتعد التغييرات ظاهرة شائعة في صناعة التشييد، إذ لا يكاد يخلوا مشروع من المشاريع من حدوث تغييرات على المخططات أو المواصفات أو مجال العمل أو شروط التعاقد. إن عملية التشييد التقليدية المتبعة في سوريا والتي يكون فيها فاصل زمني كبير بين التخطيط والتصميم والتنفيذ تزيد بشكل كبير من احتمال حدوث تغييرات وأوامر تغيير في المشروع. هناك العديد من الأسباب التي تؤدي إلى حدوث تغييرات في مشروعات التشييد، وغالبا ما تؤدي هذه التغييرات إلى زيادة في كلفة المشروعات وتأخيرات زمنية وصعوبات إدارية. وتهدف هذه الدراسة إلى تقديم فهم جيد عن الأسباب الرئيسية لأوامر التغيير وترتيبها حسب أهميتها وتأثيرها على كلفة المشروع وزمنه. حيث أظهرت الدراسة أن تدخل الجهة المالكة والأخطاء والنقص في الدراسة والتخطيط إضافة إلى شروط موقع المشروع تعد من أهم الأسباب التي تؤدي إلى إصدار أوامر تغيير في المشروع، حيث يعتبر المالك أو المهندس المشرف على المشروع الجهة صاحبة أوامر التغيير في المشروع.